1998
DOI: 10.1088/0953-8984/10/36/002
|View full text |Cite
|
Sign up to set email alerts
|

Towards the grain boundary phonon scattering problem: evidence for a low-temperature crossover

Abstract: The problem of phonon scattering by grain boundaries is studied within the wedge disclination dipole (WDD) model. It is shown that a specific q-dependence of the phonon mean free path for biaxial WDD results in a low-temperature crossover of the thermal conductivity, κ. The obtained results allow to explain the experimentally observed deviation of κ from a T 3 dependence below 0.1K in LiF and N aCl.The effect of low-angle grain boundaries on the thermal conductivity, κ, of LiF and N aCl over the temperature ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…1). In this case, the phonon-GB scattering can be expressed as [11] l −1 where ν is the Frank index, n i is the areal density of BWDDs,…”
Section: General Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In this case, the phonon-GB scattering can be expressed as [11] l −1 where ν is the Frank index, n i is the areal density of BWDDs,…”
Section: General Formalismmentioning
confidence: 99%
“…The GB-induced phonon scattering has a marked impact on the thermal conductivity, κ, at low temperatures. In bulk materials, the well-pronounced crossover from κ ∼ T 2 to κ ∼ T 3 has been proved with the crossover temperature strongly depending on the GB size [11,12]. Therefore, one can expect a similar effect in two-dimensional polycrystalline materials like graphene.…”
Section: Introductionmentioning
confidence: 97%
“…Actually, we reexamine the old ideas of the previous two paragraphs from another point of view. The model proposed here was inspired by a recent finding that a biaxial WDD is a rather unique scatterer [18]. Namely, it has been shown that the mean free path l D of thermal phonons scattered by biaxial WDD with nonskew axes of rotation behaves like l D ∼ q −1 at small q while l D → const with q increasing.…”
mentioning
confidence: 98%
“…It has long been known that there is a close connection between grain boundaries in materials with pronounced cluster structure and wedge disclination dipoles (WDD) [17]. Recently, this analogy has been successfully applied for description of the old experiments in polycrystals on the basis of the WDD-induced scattering [18]. As was mentioned in [3], the scattering in polycrystals has a close parallel in amorphous solids.Another approach which takes into account topological defects in glasses came from geometrical and topological considerations.…”
mentioning
confidence: 99%
See 1 more Smart Citation